Lyapunov-Type Inequalities for Quasilinear Systems with Antiperiodic Boundary Conditions - Bai, Yongzhen; Li, Yannan; Wang, Youyu (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish some new Lyapunov-type inequalities for one-dimensional p-Laplacian systems with antiperiodic boundary conditions. The lower bounds of eigenvalues are presented.